Phototoxic Effect of Visible Blue Light on Aggregatibacter Actinomycetemcomitans and Porphyromonas Gingivalis isolated from Patients with Chronic Periodontitis: An in Vitro Experimental Study - Al-Hamzi, Mohsen Ali; Al-Jorany, Ayman Ahmed Ahmed; Al-Shamahy, Hassan A.; Al-Sharani, Amani Abdulhakeem (Society of Pharmaceutical and Medical Professionals (SPMP), 2019)
Chronic periodentitis is a quite common disease in adult patients characterized by pocket formation and/or recession while progressive loss of periodontal attachment occurs slowly to moderately local risk factors, e.g. bacterial plaque. Wide array of microorganisms have been associated with periodontal disease, out of which Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) have been predominantly associated with periodontal diseases. The objectives of this study were to determine phototoxic effect of visible blue light on Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis clinical isolates from chronic periodentitis patients, and to study their antibiotic sensitivity against selected antibiotics. The test was carried out on 15 strains of Aggregatibacter actinomycetemcomitans and 15 strains of Porphyromonas gingivalis isolated from pockets of chronic periodentitis patients aged between 30-50 years old with pocket depths of 5-6 mm. The bacteria cultured, isolated, and identified by standard bacteriological methods, then subjected to visible blue light at different periods of time exposures. After light exposure, the bacterial killing rates were calculated from colony forming unit (CFU) counts after 48hours of anaerobic incubation. There was a decrease in CFU for both microorganisms as we proceeded from zero, 20, 40 and 60 seconds of blue light exposure. In conclusions, there was a phototoxic effect for the visible blue light emitted from the light curing device against the anaerobic periodontal pathogens and blue light exposure is effective in reducing periodontal pathogens. It is recommended that an adjunctive exogenous photosensitizer be used and that pathogens be exposed to visible light for clinical antimicrobial periodontal therapy.